Journalist at Crossroad: Balancing Privacy Rights, Ethics, and Public Right to Know in Nigeria - Luka, Luka Joshua; Idi, Shadrach (Darul Yasin Al Sys, 2025)
The Nigerian media landscape is undergoing significant transformation as journalists confront the complex task of balancing individuals’ rights to privacy with the public's right to information. This seminar paper explores the constitutional, ethical, and practical tensions inherent in navigating these dual responsibilities. Anchored in the legal provisions of Section 37 and Section 39 of the 1999 Nigerian Constitution, the study critically examines how journalists interpret and apply these rights in practice. The analysis extends to the evolving role of social media, investigative journalism, and digital reporting, which have further complicated the ethical boundaries of journalistic practice. Drawing on legal frameworks, professional ethical codes, and illustrative case studies, the paper identifies the key challenges and dilemmas confronting Nigerian journalists, including invasion of privacy, sensationalism, and the erosion of public trust. It concludes with actionable recommendations aimed at promoting ethical balance and accountability within the media sector. These include the reinforcement of ethical training, the development of newsroom policies on privacy and public interest, and greater awareness of media law among practitioners. The paper underscores the urgent need for a journalism culture that respects individual rights while fulfilling its democratic duty to inform the public.